Availability of laparoscopic surgery in Mexico's public health system: a nationwide retrospective analysisResearch in context - Mayte Bryce-Alberti; Letícia Nunes Campos; Tanujit Dey; Diana D. del Valle; Sarah K. Hill; Mehreen Zaigham; Alejandro Vela; Sabrina Juran; Geoffrey A. Anderson; Tarsicio Uribe-Leitz (Elsevier, 2023)
Summary: Background: Laparoscopic surgery remains limited in low-resource settings. We aimed to examine its use in Mexico and determine associated factors. Methods: By querying open-source databases, we conducted a nationwide retrospective analysis of three common surgical procedures (i.e., cholecystectomies, appendectomies, and inguinal hernia repairs) performed in Mexican public hospitals in 2021. Procedures were classified as laparoscopic based on ICD-9 codes. We extracted patient (e.g., insurance status), clinical (e.g., anaesthesia technique), and geographic data (e.g., region) from procedures performed in hospitals and ambulatories. Multivariable analysis with random forest modelling was performed to identify associated factors and their importance in adopting laparoscopic approach. Findings: We included 97,234 surgical procedures across 676 public hospitals. In total, 16,061 (16.5%) were performed using laparoscopic approaches, which were less common across all procedure categories. The proportion of laparoscopic procedures per 100,000 inhabitants was highest in the northwest (22.2%, 16/72) while the southeast had the lowest (8.3%, 13/155). Significant factors associated with a laparoscopic approach were female sex, number of municipality inhabitants, region, anaesthesia technique, and type of procedure. The number of municipality inhabitants had the highest contribution to the multivariable model. Interpretation: Laparoscopic procedures were more commonly performed in highly populated, urban, and wealthy northern areas. Access to laparoscopic techniques was mostly influenced by the conditions of the settings where procedures are performed, rather than patients' non-modifiable characteristics. These findings call for tailored interventions to sustainably address equitable access to minimally invasive surgery in Mexico. Funding: None.